Religiosity, Financial Vulnerability, Financial Behavior and Family Welfare in Families Receiving Direct Cash Assistance (BLT) - Fitri Ayu Wahyuni; Istiqlaliyah Muflikhati; Irni Rahmayani Johan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The government has made several efforts to reduce poverty, one of which is the provision of Direct Cash Transfer (BLT), which is expected to increase purchasing power and have an impact on increasing family welfare. The purpose of this study was to analyse the effect of religiosity, financial vulnerability and financial behaviour on family welfare in families receiving Direct Cash Transfer (DCT). This study adopted a quantitative approach using a convenience sampling technique with a total of 130 BLT recipient families as respondents. The study was conducted in Purwakarta Regency. The results showed that religiosity was in the high category, financial vulnerability was in the medium category, financial behaviour of BLT recipient families was in the low category, and family welfare was in the medium category. The results showed that family welfare is directly influenced by financial behaviour and financial vulnerability. Meanwhile, religiosity affects family welfare through financial behaviour. The results of this study show the importance of good financial behaviour for BLT recipients to improve family welfare and not depend on government assistance.